PENGARUH HABITUASI, MEDIA SOSIAL DAN PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN TERHADAP KESADARAN LINGKUNGAN SISWA SMA NEGERI SE-KOTA BANDUNG - Meidi Saputra; Dasim Budimansyah (Jurnal Ilmiah Mimbar Demokrasi, 2016)
The purpose of this research is to describe and analyze the effect of habituation, social media and Civic Education learning towards environmental awareness of senior high school students in Bandung. The hypothesis of this research is that there is the effect of habituation, social media, and Civic Education learning towards environmental awareness of senior high school in Bandung. The research was conducted by using explanatory survey method with two stage technique cluster random sampling. The research subjects are students of senior high school in Bandung. The research sample consisted of 98 students. Data were analyzed using path analysis. The findings in this research are, first, habituation, social media, and Civic Education learning in a positive and significant effect on environmental awareness with high category (R Square 0.676) contributed 67.6% to the environmental awareness of students of senior high school in Bandung. Second, there is no significant relationship between gender with environmental awareness, majoring in environmental awareness, and parental employment status with environmental awareness.